Career Management Skills Factors in Implementing Policy Successfully / Concept Note Commissioned by ELGPN - Gravina Dorianne; Lovsin Miha (European Lifelong Guidance Policy Network, 2012)
This concept note aims to identify elements that support policy development and implementation in relation to CMS, as well as those that can prove to be an obstacle to policy implementation. Introduction, The Policy to be Implemented, The People Involved in the Implementation, The Place of Implementation, The Page Dimension, Conclusion, Appendix: Interesting/ Successful Examples of CMS Policy Implementation, Austria, Czech Republic, Germany, Hungary, Lithuania, Malta, Portugal.